On the relation between the Maximum Entropy Principle and the Principle of Least Effort - Egghe, L.; Lafouge, T. (Mathematical and computer modelling, 2006)
The Maximum Entropy Principle (MEP) maximises the entropy subject to the constraint that the effort remains constant. The Principle of Least Effort (PLE) minimises the effort subject to the constraint that the entropy remains constant. The paper investigates the relation between these two principles. It is shown that (MEP) is equivalent with the principle “(PLE) or (PME)” where (PME) is (introduced in this paper) the Principle of Most Effort, meaning that the effort is maximised subject to the constraint that the entropy remains constant.